(untitled) (Journal of the College of Basic Education, 2023)
The issue of education is of great importance as it is the basic foundation for human formation in developed societies. Here, reference can be made to the reality of education in Iraq, from the Ottoman rule until the establishment of modern universities and institutes. Education, including the establishment of a school under the name (School of Staff), the aim of its establishment was the participation of all categories and those qualified to manage government departments, and he worked to develop a curriculum for it according to his plan to advance the cultural and educational level, as its curriculum included the principles of architecture, road engineering, agriculture and military sciences, as well as the establishment of a school specialized in science Engineering called the School of Engineering.